KORELASI PENGETAHUAN TERHADAP STATUS GIZI PADA MAHASISWA AKADEMI KEBIDANAN YLPP PURWOKERTO - Trisnawati, Yuli; Anasari, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Teenagers are biosocial and cultural subjects who have unique nutritional needs when viewed from a biological, psychological and social point of view. One's nutritional status can be determined by measuring body mass index. Nutritional problems that often occur in adolescents are lack of nutrient intake which results in malnutrition which is too thin which can lead to chronic energy deficiency (KEK) and can be exposed to iron deficiency anemia. This nutritional problem has a high risk of pregnancy, childbirth, childbirth and babies born. The status of nutrition is influenced by several factors, namely environmental factors, socio-economic, cognitive, biological, lifestyle, and health status. Knowledge of nutrition is a person's ability to recall the nutritional content of food and the use of these nutrients in the body. This knowledge of nutrition includes the cognitive processes needed to combine nutritional information with eating behavior, so that a good structure of knowledge about nutrition and health can be developed. If the knowledge of adolescents about malnutrition, then the efforts made by adolescents to maintain the balance of food consumed with those needed will decrease and cause problems of malnutrition or over nutrition. Based on the background above, a study was conducted on the correlation of knowledge about nutrition with nutritional status in students at midwifery academies. YLPP Purwokerto. The purpose of this study was to determine the level of knowledge, nutritional status of students, and the relationship between knowledge and nutritional status at YLPP Purwokerto midwifery students. This research is a descriptive study with a cross sectional approach. Data used in the form of primary data, collecting data using a questionnaire. The population in this study were 82 students of the YLPP Purwokerto midwifery academy. The sample in this study was accidental sampling with 41 respondents. Data analysis using the Kendall test know. The results of the study of most respondents were quite good (41%), the nutritional status of most (73%) was normal, and there was no correlation between the level of knowledge and nutritional status with a value of p = 0.348 Keywords: knowledge, nutritional status